Line-End Voltage and Voltage Profile along Power Distribution Line with Large-Power Photovoltaic Generation System - Toshiro Matsumura; Masumi Tsukamoto; Akihiro Tsusaka; Kazuto Yukita; Yasuyuki Goto; Yasunobu Yokomizu; Kento Tatewaki; Daisuke Iioka; Hirotaka Shimizu; Yuuki Kanazawa; Hiroyuki Ishikawa; Akimori Matsuo; et al. (International Journal of Photoenergy)
In recent years, the introduction of the photovoltaic generation system (PV system) has been increasing by promoting the use of renewable energy. It has been feared that the reverse current from the PV system may cause an unacceptable level of voltage rise at the interconnection node in the power distribution system. This paper discusses the effects of the reverse current on the voltage rise and fall characteristics of the interconnection node and the voltage profiles along the power distribution line. When the line current on the circuit is small, the voltage on the line monotonically increases from the sending end to the receiving end. When a relatively large current flows, it causes a voltage reduction near the distribution substation. Furthermore, on the basis of the voltage aspects in the power distribution system with a large PV system, the allowable limits of the line current and the output power from PV system are investigated.